Manajemen Motivasi Islam: (Studi Kasus di Pondok Pesantren Al-Mumtaz Banguntapan, Bantul D.I.Y. Tahun 2012) - Khanafi Khanafi; Hidayatullah Hidayatullah (Sekolah Tinggi Ilmu Tarbiyah Hidayatullah Batam, 2022)
Work motivation in Islamic education environment is still floating. On the one hand there are those who have high work motivation but still refer to western motivation theory, while on the other hand they seem to have no work motivation at all. Whereas the majority of the Indonesian population is Muslim, which of course has its own values ​​that are different from the western world, including values ​​about motivation. This study seeks to present a model of motivation development in an Islamic perspective which was carried out at the Al-Mumtaz Islamic Boarding School, Banguntapan, Bantul DIY. This research is afield research, which is qualitative in nature, with quite a lot of additions in exploring the theory. The approach used is management science and Islamic psychology. Obtaining data through the mechanism of interviews, observation, and data documentation. Management of motivation at Pondok Pesantren Al-Mumtaz Banguntapan, Bantul, DIY in general can run well because it is influenced by the main figure (kyai) who is quite competent in his field, has high integrity, has leadership and managerial spirit, and has exemplary (uswatun hasanah).